Shear failure of geometrically similar RC shear walls: Mesoscopic modellings and analysis. (May 2023) - Jin, Liu; Miao, Liyue; Du, Xiuli
Abstract: Reinforced concrete (RC) shear wall often exhibits a brittle failure pattern, which may present an obvious size effect. The objective of this study is to explore the size effect on RC shear walls with shear failure. The failure of RC shear walls having different structural sizes and aspect ratio of 1.0 was simulated by a two-dimensional mesoscopic simulated method. In 2D simulation, the concrete heterogeneities and concrete/steel interactions were explicitly considered. The mesoscopic simulation method was first verified with the available experiment observations, and was utilized to study the influences of axial load ratio and horizontal reinforcement ratio on the failure of RC shear walls having different structural sizes. The results indicate that: 1) the simulated RC shear walls present brittle failure patterns, exhibiting obvious size effect; 2) the increase of horizontal reinforcement ratio improves the shear bearing capacity of shear walls, while it would weaken or even suppress the size effect on nominal shear strength; and 3) the increasing axial load ratios improve the shear bearing capacity and lead to a stronger size effect. Moreover, a novel size effect law was proposed considering the quantitative effects from horizontal reinforcement ratios and axial load ratios for size effect.